Sedation with dexmedetomidine versus propofol during regional anaesthesia: comparing haemodynamic parameters, respiratory rates and offset times - Nadia, MN; Samsul Johari, MA; Muhammad, M; Raha, AR; Nurlia, Y (Department of Surgery, UKM Medical Centre, 2012)
This study aimed to compare dexmedetomidine and propofol, in terms of haemodynamic parameters, respiratory rates and offset times, when used for sedation in patients undergoing elective orthopaedic and surgical procedures under regional anaesthesia. This was a prospective, randomised, single-blind study where 88 patients were recruited. Patients were randomised into two groups to receive either dexmedetomidine or propofol infusion. Central neuraxial blockade (spinal, epidural or combined spinal epidural) was performed. After ensuring an adequate block and stable haemodynamic parameters, dexmedetomidine was infused 15 minutes later at 0.4 μg/kg/hr, and propofol, at a target concentration of 2.5 μg/ml. Both drugs were titrated to achieve a bispectral index score of 70 before surgery commenced. Sedation level was monitored using the bispectral index score and assessed by the Observer Assessment of Alertness Scale score. Drug infusion was adjusted to maintain bispectral index scores ranging between 70-80 during surgery. Both groups showed reductions in mean arterial pressure and heart rate from baseline readings throughout the infusion time. However there was no significant reduction in the first 15 minutes from baseline (p > 0.05). Haemodynamic parameters and respiratory rate between both groups were not significantly different (p > 0.05). No patient demonstrated significant respiratory depression or SpO2 ≤ 95%. Offset times were also not significantly different between both groups (p = 0.594). There were no significant differences in haemodynamic parameters, respiratory rates and offset times between dexmedetomidine and propofol used for sedation in patients undergoing elective orthopaedic and surgical procedures under regional anaesthesia.